2008
DOI: 10.1071/ah080210
|View full text |Cite
|
Sign up to set email alerts
|

Care management for older people with mental health problems: from evidence to practice

Abstract: Aim: To explore the implications of providing intensive care management in a typical old age mental health service in North West England. Methods:The time spent by core groups of specialist mental health and social services staff on a range of activities deemed central to the provision of intensive care management was explored by means of a diary exercise. The difference between what is actually being done and what evidence suggests is needed was examined.Results: More than 1500 hours of activity were appraise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Reflecting this, subsequent research has suggested that components of intensive care management, essential to support people at home, were rarely in place in local authorities in England. 50…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reflecting this, subsequent research has suggested that components of intensive care management, essential to support people at home, were rarely in place in local authorities in England. 50…”
Section: Discussionmentioning
confidence: 99%
“…49 Effective systems for screening, prioritising and gatekeeping access to care coordination services permit the identification of service users with complex needs. 50 These features have been specified in policy guidance over many years in England [51][52][53] and were identified as precursors to intensive care management. 50 Three measures of differentiation have been explored in this study.…”
Section: Measures Of Care Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this activities were categorised according to three themes: direct care, indirect care and team or service development as described in Table 3. The fourth category contained residual activities not captured in any of the principal themes (Challis et al, 2007(Challis et al, , 2012Jacobs et al, 2006Jacobs et al, , 2013Tucker et al, 2008;Weinberg et al, 2003). The schedule comprised a list of activities and a diary grid (Monday to Friday, 8 a.m. to 7 p.m.) divided into 30-minute intervals.…”
Section: Construction Of Diary Schedulementioning
confidence: 99%
“…Roles not already classified (Challis et al, 2007(Challis et al, , 2012Jacobs et al, 2006Jacobs et al, , 2013Tucker et al, 2008;Weinberg et al, 2003).…”
Section: Direct Carementioning
confidence: 99%